2014
DOI: 10.4028/www.scientific.net/amr.898.128
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of NiO-LSCM/LSCM Dual Composite Anode for IT-SOFC

Abstract: The LSCM (La0.7Sr0.3Cr0.5Mn0.5O3-δ) powders were synthesized by glycine-nitrate process (GNP). An anode functional layer (AFL) LSCM was fabricated on an porous NiO-LSCM anode substrate by slurry spin coating. The effect of pore-former, sintering temperature and sintering time on the quality of thin film was investigated. The film with good apparent morphology was obtained when the operating parameters were fixed as follows: the pore-former is ethyl cellulose, the content of ethyl cellulose is 5 wt.%, the sinte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…19 In addition, Ni adhesion to the surface of the LSCM substrate helps improve the conductivity and catalytic activity of the anode support. 20 However, Ni-based catalysts are susceptible to carbon deposits and deactivate during long-term use, and have high tendencies to sinter, which may deteriorate their battery performance. 21 The use of different metal-based catalysts, such as alloys of nickel and copper or cobalt, can improve the catalytic stability and coke resistance by optimizing the catalytic activity of SOFC anodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 In addition, Ni adhesion to the surface of the LSCM substrate helps improve the conductivity and catalytic activity of the anode support. 20 However, Ni-based catalysts are susceptible to carbon deposits and deactivate during long-term use, and have high tendencies to sinter, which may deteriorate their battery performance. 21 The use of different metal-based catalysts, such as alloys of nickel and copper or cobalt, can improve the catalytic stability and coke resistance by optimizing the catalytic activity of SOFC anodes.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that strontium and strontium chromate La 0.75 Sr 0.25 Cr 0.5 Mn 0.5 O 3− δ (LSCM) are promising substitute anode materials 17,18 for Ni–YSZ cermet, and they exhibit stable performance as a catalytic material for H 2 and CH 4 redox when a low steam to hydrocarbon ratio is used 19 . In addition, Ni adhesion to the surface of the LSCM substrate helps improve the conductivity and catalytic activity of the anode support 20 . However, Ni‐based catalysts are susceptible to carbon deposits and deactivate during long‐term use, and have high tendencies to sinter, which may deteriorate their battery performance 21 .…”
Section: Introductionmentioning
confidence: 99%